Almost Fare Free: Impact of a Cheap Public Transport Ticket on Mobility Patterns and Infrastructure Quality - Mario Liebensteiner; Jakob Losert; Sarah Necker; Florian Neumeier; Jörg Paetzold; Sebastian Wichert (CESifo GmbH, 2024)
In 2022, Germany introduced a temporary 9-euro monthly ticket for unlimited local and regional public transport. We investigate its impact on mobility patterns, including increased public transport usage, reduced car traffic, and rail network congestion. Using difference-in-difference and event-study analyses with mobile network-based mobility, traffic volume, and rail traffic data, we find limited substitution between transportation modes, a strong increase in leisure train journeys, and notable adverse effects on rail infrastructure quality. These effects dissipate after the ticket's expiration. Our study suggests caution regarding the expected environmental benefits of nearly fare-free 'go-anywhere' public transport tickets, which are discussed in several countries.
Keywords: R12; R41; R42; R48; Q58; 330; fare-free public transport; mobility patterns; traffic volume; mode choice; transport subsidies